Analisis Kesalahan Penggunaan Ejaan dalam Surat Pemberitahuan di SMA Negeri 1 Jayapura: Analysis of Error Using Spelling on Notification Letter at SMA Negeri 1 Jayapura - Nurasiyah, Nurasiyah (Kibas Cenderawasih, 2023)
An official letter is an official communication medium issued by an agency that, in writing, must use the state language following linguistic rules. This study aims to describe the spelling errors used in notification letters at SMA Negeri 1 Jayapura. This research is qualitative descriptive research that describes the phenomenon accurately and objectively. The method is to study documents to obtain data from notification letter archives. The data from an analysis of seven notification letters issued in February-March 2022 totaled 164 errors. The errors consist of 66 errors in the use of letters, 54 errors in writing words, and 44 errors in the use of punctuation marks. This error was caused by the school's inconsistent use of official document layout references in the school environment, the administrative staff of the correspondence section who did not understand Indonesian spelling rules, and the business manuscript administration section who wrote letters to more than one person and used several computer devices. Its rise to the concept of writing different letters in schools.